High diversity of microalgae as a tool for the synthesis of different silver nanoparticles: A species-specific green synthesis - Moraes, Leonardo C.; Figueiredo, Rute C.; Ribeiro-Andrade, Rodrigo; Pontes-Silva, Augusto V.; Arantes, Mônica L.; Giani, Alessandra; Figueredo, Cleber C. (Colloid and interface science communications, 2021)
Autotrophic microorganisms can be useful for the green synthesis of nanoparticles (NPs), but there is a lack of knowledge to affirm if the high variety of microorganisms is connected to a potential high diversity of NPs. Here, aqueous extracts of two cyanobacteria (Synechococcus elongatus and Microcystis aeruginosa) and four microalgae (the chlorophytes Coelastrum astroideum and Desmodesmus armatus; and the charophytes Cosmarium punctulatum and Klebsormidium flaccidum) were used for the biosynthesis of silver nanoparticles (AgNPs). The nanoparticle characterization was performed by UV–Visible absorption spectrum, Fourier Transforms Infrared (FT-IR), Transmission Electron Microscopy (TEM) and Energy Dispersive X-Ray Spectroscopy (EDS). This is the first study trying to establish some connection between the taxonomical diversity of microalgae and cyanobacteria and the synthesis of different silver nanoparticles. All algal and cyanobacterial extracts resulted in the synthesis of well-disperse and crystalline AgNPs, with no agglomerate formation. TEM analysis showed spherical AgNPs shape with size range within 1.8–5.4 nm. FTIR analysis demonstrated the presence of hydroxyl groups of peptidoglycan nature acting as stabilizing agents in the surface of the AgNPs. The nanoparticle shape and kind of stabilizing biomolecules were highly similar, but their size was significantly different, which can affect the NP properties. There was no pattern for the AgNPs in terms of the microorganism phyla. Our results showed a very high potential for the use of cyanobacteria and microalgae in the green synthesis of NPs since the variety of AgNPs obtained was species-specific. [Display omitted] •The many uses of nanoparticles (NPs) depends on their composition and structure.•The traditional synthesis of metal NPs results in environmental impacts.•Microorganisms can be applied for eco-friendly green synthesis of NPs.•Cyanobacteria and algae showed a species-specific synthesis of silver NPs.•Cyanobacteria and algae have high potential for expand silver NPs types and uses.